A framework for providing e-services to the rural areas using wireless ad hoc and sensor networks - Pathan, Al-Sakib Khan; Islam, Humayun Kadir; Sayeed, Sabit Anjum; Ahmed, Farruk; Hong, Choong Seon (2006)
In recent years, the proliferation of mobile computing devices has driven a revolutionary change in the computing world. The nature of ubiquitous devices makes wireless networks the easiest solution for their interconnection. This has led to the rapid growth of several wireless systems like wireless ad hoc networks, wireless sensor networks etc. In this paper we have proposed a framework for rural development by providing various e-services to the rural areas with the help of wireless ad hoc and sensor networks. We have discussed how timely and accurate information could be collected from the rural areas using wireless technologies. In addition to this, we have also mentioned the technical and operational challenges that could hinder the implementation of such a framework in the rural areas in the developing countries.